AgCuI2 single crystal as well as preparation method and application thereof

By preparing AgCuI2 single crystal, the challenges of existing photoelectric semiconductor materials in terms of stability and carrier mobility are solved, and efficient photoelectric performance and good thermal stability are achieved, which are suitable for hole transport layer materials of solar cell devices.

CN119843366APending Publication Date: 2025-04-18XUCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991698.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing optoelectronic semiconductor materials have challenges in environmental sensitivity, grain boundary and defect problems, limitations in carrier mobility, as well as production costs and energy consumption, making it difficult to meet the needs of efficient optoelectronic devices.

Method used

A single AgCuI2 crystal was prepared, and AgI was uniformly ground and then added to HI solution for hydrothermal reaction, thereby obtaining AgCuI2 single crystal with excellent stability and good photoelectric properties.

Benefits of technology

AgCuI2 single crystal exhibits excellent thermal stability and good carrier separation and transmission performance, with a band gap width of 2.63 eV. It is suitable for hole transport layer materials in halide perovskite solar cell devices and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843366A_ABST
    Figure CN119843366A_ABST
Patent Text Reader

Abstract

The invention discloses an AgCuI2 single crystal structure as well as a preparation method and application thereof, and belongs to the technical field of photoelectric semiconductor materials. The AgCuI2 single crystal belongs to a cubic system, the space group is F-43m, and the unit cell volume # imgabs0 # unit cell parameter is # imgabs1 # alpha = beta = gamma = 90 degrees. The preparation method comprises the following steps: grinding and uniformly mixing CuI and AgI, adding 20-30wt% of HI solution to obtain a precursor solution, and carrying out hydrothermal reaction at the temperature of 120-180 DEG C to obtain the CuI / AgI composite material. The AgCuI2 single crystal prepared by the preparation method disclosed by the invention shows excellent thermal stability and photoelectric characteristics, and the wide band gap of the AgCuI2 single crystal reaches 2.63 eV. As a wide bandgap ternary compound semiconductor material, the AgCuI2 single crystal is very suitable for being used as a hole transport layer in a halide perovskite solar cell, which indicates that the AgCuI2 single crystal has wide application potential in the technical field of solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic semiconductor materials, and specifically relates to an AgCuI 2 Single crystal and its preparation method and application. Background Art

[0002] The development of optoelectronic semiconductor materials is crucial to the development of modern science and technology and industry. They not only improve the performance of optoelectronic devices, promote the development of new energy, and support the development of high-tech industries, but also play a key role in ensuring national security, promoting the construction of an information society, and realizing environmentally friendly energy. In particular, the new generation of semiconductor materials represented by VIIA group iodides have become a strategic commanding height in the field of international optoelectronic information technology, leading the clean energy revolution in the fields of new energy vehicles, 5G communications, and photovoltaic power generation. Transition element halides have gradually emerged in the optoelectronic field due to their unique optoelectronic properties and have become one of the important materials.

[0003] Optoelectronic semiconductor materials, such as gallium phosphide, lead compounds, cadmium compounds, and transition metal dichalcogenides, play a vital role in the field of optoelectronic devices due to their efficient photoelectric conversion capabilities, optical stability, thermal stability, and excellent electrical properties. However, these materials also face a series of challenges, including sensitivity to the environment, grain boundary and defect problems, carrier mobility limitations, and production costs and energy consumption. In order to overcome these problems, continuous research and technological innovation are needed to achieve wider applications and improve optoelectronic performance. Summary of the invention

[0004] The purpose of the present invention is to provide a AgCuI 2 Single crystal and its preparation method and application. AgCuI 2 The single crystal has excellent stability and is a P-type semiconductor with good photoelectric properties.

[0005] Provide a AgCuI 2 Single crystal, the single crystal structure belongs to the cubic system, the space group is F-43m, the unit cell volume The unit cell parameters are α=β=γ=90°.

[0006] According to the above scheme, the AgCuI 2 The single crystal has a band gap of 2.63 eV.

[0007] According to the above scheme, the AgCuI 2 The single crystal size is 0.5-2mm.

[0008] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0009] 1) Grind and mix CuI and AgI evenly, add 20-30wt% HI solution, stir and dissolve to obtain a precursor solution;

[0010] 2) The precursor solution obtained in step 1) is subjected to a hydrothermal reaction at a temperature of 120-180°C. After the reaction is completed, the solid is separated, washed with water to remove HI, and vacuum dried to obtain AgCuI 2 Single crystal.

[0011] According to the above scheme, in step 1), the molar ratio of CuI to AgI is 0.5-1.5:1.

[0012] According to the above scheme, in step 1), preferably, the molar volume of AgI and HI solution is: 1 mmol: 2-4 mL.

[0013] According to the above scheme, in step 2), the hydrothermal reaction time is 24-48h.

[0014] According to the above scheme, in step 2), when HI is removed by water washing, the solution after washing is neutral.

[0015] According to the above scheme, in step 2), the vacuum drying temperature is 40-100°C and the time is 24-48h.

[0016] According to the above scheme, in step 1), the concentration of the HI solution is preferably 25-30 wt%.

[0017] According to the above scheme, in step 1), the temperature of the hydrothermal reaction is preferably 120-150°C.

[0018] Provided is a AgCuI 2 Application of single crystals as hole transport layer materials in halide perovskite solar cell devices.

[0019] The beneficial effects of the present invention are as follows:

[0020] 1. AgCuI provided by the present invention 2 Single crystal, with excellent thermal stability, good carrier separation and transport performance, good photoelectric performance, is a ternary wide bandgap semiconductor with a bandgap width of 2.63eV. It can be used as a hole transport layer material in halide perovskite solar cell devices and has good application prospects in the field of solar cells.

[0021] 2. This invention successfully prepared AgCuI for the first time through hydrothermal reaction at low temperature 2 Single crystals have a simple preparation method, mild conditions, short time, low cost, and no need to use organic solvents. They are green and environmentally friendly, and are conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the AgCuI in Example 1 2 Actual picture of single crystal.

[0023] Figure 2 is the AgCuI in Example 1 2 Scanning electron microscope (SEM) image of a single crystal.

[0024] Figure 3 It is AgCuI in Example 2 2 X-ray diffraction (XRD) pattern of single crystal.

[0025] Figure 4 It is AgCuI in Example 2 2 Thermogravimetric analysis (TGA) of a single crystal.

[0026] Figure 5 It is AgCuI in Example 2 2 Scanning electron microscope (SEM) image of a single crystal.

[0027] Figure 6 The AgCuI obtained by SC-XRD test in Example 2 2 Schematic diagram of the structure of a single crystal.

[0028] Figure 7 is the AgCuI in Example 3 2 Transient photovoltage (TPV) plot of a single crystal.

[0029] Figure 8 is the AgCuI in Example 3 2 X-ray diffraction (XRD) pattern of single crystal.

[0030] Fig. 9 It is AgCuI in Example 4 2 Scanning electron microscope (SEM) image of a single crystal.

[0031] Fig.10 It is AgCuI in Example 4 2 Transient photovoltage (TPV) plot of a single crystal.

[0032] Fig.11 is the AgCuI in Example 5 2 X-ray diffraction (XRD) pattern of single crystal.

[0033] Fig.12 It is AgCuI in Example 6 2 X-ray diffraction (XRD) pattern of single crystal. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below in conjunction with specific implementations and with reference to the accompanying drawings.

[0035] Example 1

[0036] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0037] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 20 wt% HI into the bottle, stir, sonicate, and dissolve to obtain a precursor solution.

[0038] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0039] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 120°C, maintain the constant temperature for 24 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0040] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral; put the obtained solid into a vacuum drying oven and vacuum dry it at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0041] Figure 1 In this embodiment, AgCuI 2 Physical pictures of single crystals; Figure 2 In this embodiment, AgCuI 2 Scanning electron microscope (SEM) image of a single crystal. As can be seen from the image, AgCuI 2 The single crystal is a yellowish crystal, and from the SEM image it can be seen that the crystal grows in a unique way and along a specific orientation.

[0042] Example 2

[0043] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0044] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 25 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0045] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0046] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 120°C, maintain the constant temperature for 24 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0047] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral; put the obtained solid into a vacuum drying oven and vacuum dry it at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0048] Figure 3 In this embodiment, AgCuI 2 X-ray diffraction (XRD) diagram of single crystal; it can be seen from the XRD diagram that at a concentration of 25% HI, the diffraction peak of the generated crystal is stronger, proving that its crystallinity is better.

[0049] Figure 4 In this embodiment, AgCuI 2 Thermogravimetric analysis (TGA) of the single crystal; it can be seen from the TGA graph that the crystal does not undergo any reaction before 500°C, proving that the crystal has good stability.

[0050] Figure 5 In this embodiment, AgCuI 2 Scanning electron microscope (SEM) image of single crystal; From the SEM image, we can see that AgCuI 2 Growth pattern of single crystal.

[0051] Figure 6 In this embodiment, AgCuI 2 The single crystal structure diagram of the single crystal. The single crystal in this embodiment is first subjected to SC-XRD test, and then the test results are analyzed to obtain AgCuI 2 The single crystal structure of the single crystal. From the single crystal structure diagram combined with the specific analysis, we can know the specific spatial arrangement of Ag, Cu and I. The crystal is a cubic system with a space group of F-43m. From the specific SC-XRD analysis, we can know that the unit cell volume of the crystal is have The unit cell parameters are α=β=γ=90°. Meanwhile, the structural data obtained by the SC-XRD test of this embodiment is used as the standard reference sample of the XRD diagrams of other embodiments.

[0052] Example 3

[0053] Provide a AgCuI 2The method for preparing a single crystal comprises the following steps:

[0054] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 30 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0055] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0056] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 120°C, maintain the constant temperature for 24 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0057] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral, and put the obtained solid into a vacuum drying oven at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0058] Figure 7 In this embodiment, AgCuI 2 Transient photovoltage (TPV) diagram of single crystal; Figure 8 In this embodiment, AgCuI 2 X-ray diffraction (XRD) pattern of single crystal. From the TPV pattern, it can be seen that the prepared crystal is a P-type semiconductor with a carrier separation time of 3.67×10 -7 s, and the carrier recombination time is 4.99×10 -3 s and the maximum response signal is -0.11V.

[0059] Comparative Example 1

[0060] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 35 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0061] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0062] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 120°C, maintain the constant temperature for 48 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0063] Step 4: Take out the glass bottle from the reactor and no crystals are generated.

[0064] Example 4

[0065] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0066] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 25 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0067] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0068] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 150°C, maintain the constant temperature for 48 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0069] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral, and put the obtained solid into a vacuum drying oven at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0070] Fig. 9 In this embodiment, AgCuI 2 Scanning electron microscope (SEM) image of single crystal; Fig.10 In this embodiment, AgCuI 2 Transient photovoltage (TPV) diagram of the single crystal. From the TPV diagram, it can be seen that the response signal has increased and the carrier separation time is 3.1×10 -7 s, and the carrier recombination time is 4.63×10 -3 s and the maximum response signal is -0.14V.

[0071] Example 5

[0072] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0073] Step 1: Weigh 0.001 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 25 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0074] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0075] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 180°C, maintain the constant temperature for 48 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it cools down to room temperature, open the air drying oven and take out the reactor.

[0076] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral, and put the obtained solid into a vacuum drying oven at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0077] Fig.11 In this embodiment, AgCuI 2 X-ray diffraction (XRD) pattern of single crystal.

[0078] Example 6

[0079] Provide a AgCuI 2 The method for preparing a single crystal comprises the following steps:

[0080] Step 1: Weigh 0.0015 mol of CuI and 0.001 mol of AgI solid, put them into a mortar, grind them to mix them evenly, and then transfer them to a 10 mL glass bottle. Add 4 mL of 25 wt% HI into the bottle, stir, ultrasonicate, and dissolve. Obtain a precursor solution.

[0081] Step 2: Transfer the open glass bottle containing the precursor solution to the reactor, tighten the metal shell, and place it in a forced air drying oven.

[0082] Step 3: Set the program of the air drying oven to: increase the temperature from room temperature to 150°C, maintain the constant temperature for 48 hours. After the reaction is completed, close the air drying oven and allow the box to cool naturally. After it drops to room temperature, open the air drying oven and take out the reactor.

[0083] Step 4: Take out the glass bottle from the reactor, rinse the solid obtained by centrifugation with deionized water to completely remove HI until the rinsed solution is neutral, and put the obtained solid into a vacuum drying oven at 80°C for 24 hours to obtain AgCuI 2 Single crystal.

[0084] Fig.12 In this embodiment, AgCuI 2 X-ray diffraction (XRD) diagram of a single crystal. It can be seen that when the feed ratio of CuI and AgI changes, AgCuI can also be precipitated. 2 Single crystal.

[0085] The samples of the above-mentioned embodiments 1-6 were characterized, and it was proved that pure AgCuI 2 Single crystal, tested AgCuI 2 Single crystals have excellent carrier separation and transport properties and good photoelectric properties. They can be used as hole transport layer materials in halide perovskite solar cell devices and have good application prospects in the field of solar cells.

[0086] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solutions of the present invention.

Claims

1. An AgCuI2 single crystal, characterized in that: The AgCuI2 single crystal structure belongs to the cubic system, the space group is F-43m, and the unit cell volume is The unit cell parameters are α=β=γ=90°.

2. The AgCuI2 single crystal according to claim 1, characterized in that The size of the AgCuI2 single crystal is 0.5-2 mm.

3. A method for preparing a AgCuI2 single crystal according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) Grind and mix CuI and AgI evenly, add 20-30wt% HI solution, stir and dissolve to obtain a precursor solution; 2) The precursor solution obtained in step 1) is subjected to a hydrothermal reaction at a temperature of 120-180° C. After the reaction is completed, the solid is separated, washed with water to remove HI, and vacuum dried to obtain a AgCuI2 single crystal.

4. The preparation method according to claim 3, characterized in that: In the step 1), the molar ratio of CuI to AgI is 0.5-1.5:

1.

5. The preparation method according to claim 3, characterized in that: In the step 2), the hydrothermal reaction time is 24-48 hours.

6. The preparation method according to claim 3, characterized in that: In the step 1), the concentration of the HI solution is 25-30 wt%.

7. The preparation method according to claim 3, characterized in that: In the step 1), the temperature of the hydrothermal reaction is 120-150°C.

8. The preparation method according to claim 3, characterized in that: In the step 2), the vacuum drying temperature is 40-100° C. and the time is 24-48 hours.

9. Use of the AgCuI2 single crystal according to any one of claims 1 to 2 as a hole transport layer material in a halide perovskite solar cell device.